Relationship between consolidation tumor ratio and tumor‐infiltrating lymphocytes in small‐sized lung adenocarcinoma. Issue 15 (6th July 2022) - Ono, Yuki; Tagawa, Tetsuzo; Kinoshita, Fumihiko; Haratake, Naoki; Takada, Kazuki; Kohno, Mikihiro; Takenaka, Tomoyoshi; Kamitani, Takeshi; Shimokawa, Mototsugu; Oda, Yoshinao; Mori, Masaki; Yoshizumi, Tomoharu
Abstract: Background: Consolidation tumor ratio (CTR) is associated with cancer progression and histological invasiveness in lung adenocarcinoma (LAD). However, little is known about the association between CTR and immune‐related factors, including tumor‐infiltrating lymphocytes (TILs) density or tumor expression of programmed death ligand 1 (PD‐L1) and indoleamine 2, 3‐dioxygenase 1 (IDO1) in small‐sized LAD. Methods: This study included 258 patients with LAD (<3 cm) who underwent surgery. Patients were assigned to four groups: CTR = 0; 0 < CTR <0.5; 0.5 ≤ CTR <1 (ground‐glass opacity [GGO] group); and CTR = 1 (pure‐solid group). CD4 +, CD8 +, and FoxP3 + TIL density and PD‐L1 and IDO1 tumor expression were assessed by immunohistochemistry. Results: Among the GGO group, CD8 + and FoxP3 + TIL density increased significantly with increasing CTR ( p < 0.001 and p < 0.001, respectively). Moreover, PD‐L1 and IDO1 expression was significantly higher in the pure‐solid group than in the GGO group ( p < 0.001 and p < 0.001, respectively). Conclusions: CTR was correlated with the abundance of CD8 + and FoxP3 + TILs in the GGO group. PD‐L1 and IDO1 positivity rates were significantly higher in the pure‐solid group than in the GGO group. Increased CTR may be correlated with immunosuppressive condition. Abstract : High CTR was correlated with the abundance of CD8 + and FoxP3 + TILs in the GGO group. PD‐L1 and IDO1 expression were significantly higher in the pure‐solid group than in the GGO group. Small‐sized LAD with high CTR might be in a more immunosuppressive state than that with low CTR in small‐sized LAD.